Emblematic illustrations in the editions dedicated to Jonušas Radvila (1612-1655) - Aistė Paliušytė (Knygotyra)
Jonušas Radvila, the hetman of the Lithuanian Grand Duchy and the voivode of Vilnius, was one of the most ambitious art as well as book patrons of the first half of the seventeenth century in the LGP. A large part of his ordered editions were occasional panegyrics. They were decorated by emblematic illustrations, which were very popular and used in books of the first half of the seventeenth century in the LGP. Heraldic emblems, glorifying the patron of the book according to the motifs of his coat of arms, were frequently used in the books ordered by Jonušas Radvila. These emblems were genetically connected with medieval devices and expressed the representative aims of a noble.